The Vulnerable System: An Analysis of the Tenerife Air Disaster - Weick, Karl E. (Journal of Management, 1990)
The Tenerife air disaster, in which a KLM 747 and a Pan Am 747 collided with a loss of 583 lives, is examined as a prototype of system vulnerability to crisis. It is concluded that the combination of interruption of important routines among interdependent systems, interdependencies that become tighter, a loss of cognitive efficiency due to autonomic arousal, and a loss of communication accuracy due to increased hierarchical distortion, created a configuration that encouraged the occurrence and rapid diffusion of multiple small errors. Implications of this prototype for future research and practice are explored.